Pengaruh Faktor Internal dan Faktor Eksternal Bank terhadap Kinerja Perusahaan Perbankan yang terdaftar di Bursa Efek Indonesia Tahun 2013-2016 - Ary Kartina; Mahben Jalil; Niken Wahyu C (Permana : Jurnal Perpajakan, Manajemen, dan Akuntansi, 2017)
The purpose of the research is 1) To test the effect of capital adequacy ratio on the performance of banking company 2) To test the influence of asset quality on the performance of banking company 3) To test the effect of management efficiency on the performance of banking company 4) To test the influence of liquidity management on the performance of banking company 5) To test the influence of the interest rate on the performance of banking companies 6) To test the effect of the inflation rate on the performance of banking companies 7) To test the effect of capital adequacy ratio, asset quality, management efficiency, liquidity management, interest rate and inflation rate on the performance of banking companies. Data collection method used in this research is documentation. While the methods of Data Analysis and Testing Hypotheses used are Classical Assumption Test, Multiple Linear Regression Analysis, Partial Testing, Simultaneous Testing, Coefficient of Determination (R Square). There is no significant effect of capital adequacy ratio on company performance, evidenced from the partial capital adequacy ratio test on banking financial performance obtained by sig value. of 0.718> 0.05. There is a significant influence of asset quality on company performance, evidenced from the result of partial asset quality test toward banking financial performance obtained by sig value. of 0.034 <0.05. There is a significant influence management efficiency on the performance of the company, evidenced from the results of partial management of eficiency test of banking financial performance obtained sig value. of 0.008 <0.05. There is a significant influence of liquidity management on company performance, evidenced from the results of partial liquidity test of banking financial performance obtained sig value. of 0.000 <0.05. There is no significant effect of interest rate on company performance, evidenced from the partial test of interest rate on banking financial performance obtained sig value. Of 0.560> 0.05. There is no significant effect of inflation rate on company performance, evidenced from result of partial test of inflation on banking financial performance obtained by sig value. of 0.819> 0.05. There is significant influence of capital adequacy ratio, asset quality, management efficiency, liquidity management, interest rate and inflation rate to company performance, evidenced from result of testing significance of multiple regression analysis obtained by sig value. of 0.000 <0.05